Risk factors for and outcomes of acute kidney injury in ward-based hospital trauma admissions: A retrospective cohort analysis. - Omar Kiwan; Elizabeth Finnimore; Benjamin D James; Paul W Robinson; Mohammed Al-Kalbani; Becky Bonfield; Darren Green (PLoS ONE)
Background Guidelines on risk assessment for acute kidney injury (AKI) are generalised and may not adequately consider atypical presentations such as trauma. Older people are largely absent in past studies of AKI after trauma, meaning there is an evidence gap of trauma-associated AKI risk factors in older people. Methods We undertook a retrospective analysis of 2,211 ward-level hospital trauma admissions during 2014-2022. We identified risk factors associated with AKI in people aged ≥65 years and <65 years, and established the clinical impact of AKI in older and younger trauma cases. Results In those aged ≥65 years, parameters significantly associated with AKI were age, CKD, heart failure, infection, lower limb trauma. In people <65 years, the significant risk factors were age, CKD, liver disease, coronary disease, and pelvic trauma. In both age groups, AKI was associated with a greater risk of length of stay >14 days but not mortality. Conclusions This study shows that risk factors for AKI in older trauma patients are comparable to those found in most guidelines for AKI risk assessment, with the addition of lower limb trauma. This factor could be considered as a useful adjunct in trauma AKI risk assessment tools to facilitate stratified care.